Conditional Variational Autoencoder and generative adversarial network-based approach for long-tailed fault diagnosis for the motor system - Huang, Mei; Sheng, Chenxing; Rao, Xiang (Measurement : journal of the International Measurement Confederation, 2025)
This study addresses the challenge of diagnosing motor faults in long-tailed data distributions, characterized by dominant healthy states and rare fault types. We propose the LT-CVAE-GAN model, which integrates a Conditional Variational Autoencoder (CVAE) with a Conditional Generative Adversarial Network (CGAN) to enhance long-tailed fault diagnosis. Initially, we train the CVAE-GAN model using traditional CVAE and CGAN losses such as Kullback–Leibler (KL) divergence loss, reconstruction loss, and adversarial loss. Additionally, we introduce mean feature matching loss and pairwise feature matching loss to mitigate mode collapse and improve model stability, thereby enhancing the generation ability of less frequent fault samples under long-tail conditions. Subsequently, the pre-trained Generator is used to produce infrequent fault mode data to rebalance the dataset. Classifier parameters are fine-tuned in this step to improve fault diagnosis accuracy. Experimental results demonstrate that our LT-CVAE-GAN surpasses state-of-the-art models in diverse long-tailed conditions. •A novel method is proposed for long-tailed fault diagnosis of the motor system.•A data augmentation-boosted method based on CVAE and GAN is proposed.•The mean feature matching loss and pairwise feature matching loss are introduced.•The LT-CVAE-GAN performs robust across four long-tailed cases.